Strategi Pemasaran Digital Berkelanjutan Berbasis Kearifan Lokal dan Inovasi Hijau untuk UMKM di Indonesia - Rini, Intan Puspita Rini; Fasyni, Tholal Fasyni; Sekarini, Ratih Ayu Sekarini (ICON Publisher, 2025)
This study explores the development of a sustainable digital marketing strategy that integrates local wisdom and green innovation to enhance the competitiveness of micro, small, and medium enterprises (MSMEs) in Indonesia. In the era of digital transformation and environmental awareness, MSMEs are required to adopt adaptive marketing approaches that align with both cultural values and sustainability principles. This research employs a qualitative descriptive method through literature review and case analysis of selected MSMEs implementing eco-friendly digital marketing initiatives. The findings reveal that integrating local cultural values—such as community cooperation (gotong royong) and environmental ethics—into digital marketing practices significantly enhances customer trust and brand loyalty. Moreover, the adoption of green innovation strengthens market differentiation while promoting sustainable consumption behavior among consumers. The study emphasizes that digital marketing sustainability requires a balance between technological utilization, environmental responsibility, and cultural authenticity. This framework contributes to the broader discourse on sustainable entrepreneurship and provides practical insights for policymakers and MSME practitioners in designing culturally embedded and environmentally responsible digital marketing strategies.